Be a brave, big-hearted rebel at work : get unstuck, gain new perspectives (O'Reilly Media, 2015)
"The more credibility and trust we have, the more likely people are to help us, support our ideas, and fund our initiatives. Here's how to determine your credibility and how a rebel can build much more, and how to determine how much you're trusted and who you can trust."--Resource description page